Preparation of anti‐migration transition layer and its application in cast‐in‐case solid rocket motors. Issue 28 (18th March 2021) - Zhang, Bowen; Li, Xiaoyu; Zhang, Weihai; Ren, Rui; Zhang, Zhaobo; Luo, Yunjun
Abstract: The polyester‐based transition layers were first synthesized with poly (diethylene glycol adipate), glycerin, and toluene diisocyanate. Then they were coated between the propellant and the liner to improve the bonding performance of the charge and inhibit the migration of the energetic plasticizer in the propellant. The effects of R value (the ratio of the quantity of isocyanate functions NCO with respect to the quantity of hydroxyl functions OH) on migration resistance and bonding performance were also studied. The overall performance was optimized at R = 1.5: after the transition layer was applied, the binding strength was greatly increased from 0.14 to 0.64 MPa, which had good application prospects. Meanwhile, due to the strong interactions between the polar ester groups and N‐butyl‐N‐nitratoethyl nitramine (NENA) in the transition layers, the portion of NENA migrating into liners were reduced from 7.6% to 6.0% (reduced by 21%), indicating that the introduction of polyester transition layers could significantly improve the anti‐migration effect. The activation energies of migration for NENA in the transition layers were about 66.3 ~ 94.3 kJ/mol, which were equivalent to the value of strong hydrogen bonding. Abstract :